Regular consumption of cod liver oil is associated with reduced basal and exercise-induced C-reactive protein levels; a prospective observational trial: A NEEDED (The North Sea Race Endurance Exercise Study) 2014 sub-study - Hansen, Mette Wærstad (J Int Soc Sports Nutr, 2021)
BACKGROUND: Dietary supplement use among recreational athletes is common, with the intention of reducing inflammation and improving recovery. We aimed to describe the relationship between omega-3 fatty acid supplement use and inflammation induced by strenuous exercise. METHODS: C-reactive protein (CRP) concentrations were measured in 1002 healthy recreational athletes before and 24 h after a 91-km bicycle race. The use of omega-3 fatty acid supplements was reported in 856 out of 1002 recreational athletes, and the association between supplement use and the exercise-induced CRP response was assessed. RESULTS: Two hundred seventy-four subjects reported regular use of omega-3 fatty acid supplements. One hundred seventy-three of these used cod liver oil (CLO). Regular users of omega-3 fatty acid supplements had significantly lower basal and exercise-induced CRP levels as compared to non-users (n = 348, p < 0.001). Compared to non-users, regular users had a 27% (95% confidence interval (CI): 14–40) reduction in Ln CRP response (unadjusted model, p < 0.001) and 16% (95% CI: 5–28, p = 0.006) reduction after adjusting for age, sex, race duration, body mass index, delta creatine kinase, MET hours per week, resting heart rate and higher education. CLO was the primary driver of this response with a 34% (95% CI: 19–49) reduction (unadjusted model, p < 0.001) compared to non-users. Corresponding numbers in the adjusted model were 24% (95% CI: 11–38, p < 0.001). CONCLUSION: Basal CRP levels were reduced, and the exercise-induced CRP response was attenuated in healthy recreational cyclists who used omega-3 fatty acid supplements regularly. This effect was only present in regular users of CLO. TRIAL REGISTRATION: NCT02166216, registered June 18, 2014 – Retrospectively registered. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12970-021-00437-1.